The Role of Tibialis Posterior Tendon Transfer in Correction of Foot Drop Deformity - Al- Iedani, Mohammed S.; Aaqail, Falah M; Majeed, Ghadeer H (AL-Kindy College Medical Journal, 2013)
Bac kground: The transfer of the tibialis posterior tendon to the anterior aspectof the ankle not only replaces the function of the paralyzed muscles, but alsoremoves the deforming force on the medial aspect of the foot.Objec t i ves : In this study, we evaluated patients who underwent tibialisposterior tendon transfer for the treatment of foot drop, and comparison throughinterosseous membrane route versus anterior to lower tibia route of tibialisposterior tendon transfer, with evaluation of the results according to carayoncriteriaMethods: Nine patients with foot drop secondary to different causes treated withtibialis posterior tendon transfer from January 2011 to January 2012 werefollowed up for a mean of 12 months in Al Kindy Teaching Hospital. We use twodifferent techniques, first transfer the tendon through the interosseousmembrane (four patients), and the second technique transfer the tendon anteriorto tibia (five patients).Resul t s : In general according to carayon evaluation criteria, the results wereexcellent in two patients (22.2%), good in five patients (55.6%), and moderate intwo patients (22.2%). Through anterior to lower tibia route, 4 patients getexcellent to good result (80%), and through interosseous route, 3patients getgood to excellent result (75%).Conc lus ions : Transfer of tibialis posterior tendon for the treatment of foot dropdeformity enables the patients to walk without the aid of orthosis and increase theirquality of life. With no differences between anterior to lower tibia route and throughinterosseous membrane route.